Disease-Associated Gut Microbiota Reduces the Profile of Secondary Bile Acids in Pediatric Nonalcoholic Fatty Liver Disease - Yu, Jiake; Zhang, Hu; Chen, Liya; Ruan, Yufei; Chen, Yiping; Liu, Qi (Frontiers in Cellular and Infection Microbiology, 2021)
Children with nonalcoholic fatty liver disease (NAFLD) display an altered gut microbiota compared with healthy children. However, little is known about the fecal bile acid profiles and their association with gut microbiota dysbiosis in pediatric NAFLD. A total of 68 children were enrolled in this study, including 32 NAFLD patients and 36 healthy children. Fecal samples were collected and analyzed by metagenomic sequencing to determine the changes in the gut microbiota of children with NAFLD, and an ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) system was used to quantify the concentrations of primary and secondary bile acids. The associations between the gut microbiota and concentrations of primary and secondary bile acids in the fecal samples were then analyzed. We found that children with NAFLD exhibited reduced levels of secondary bile acids and alterations in bile acid biotransforming-related bacteria in the feces. Notably, the decrease in Eubacterium and Ruminococcaceae bacteria, which express bile salt hydrolase and 7α-dehydroxylase, was significantly positively correlated with the level of fecal lithocholic acid (LCA). However, the level of fecal LCA was negatively associated with the abundance of the potential pathogen Escherichia coli that was enriched in children with NAFLD. Pediatric NAFLD is characterized by an altered profile of gut microbiota and fecal bile acids. This study demonstrates that the disease-associated gut microbiota is linked with decreased concentrations of secondary bile acids in the feces. The disease-associated gut microbiota likely inhibits the conversion of primary to secondary bile acids.